2014
DOI: 10.1016/j.apcata.2014.07.035
|View full text |Cite
|
Sign up to set email alerts
|

On the oligomerization mechanism of Brønsted acid-catalyzed conversion of furans to diesel-range fuels

Abstract: a b s t r a c tThe conversion of biomass to fuels and chemicals is considered to be a promising alternative to petroleumbased conventional routes. The oligomerization of biomass-derived furans can yield an important precursor toward diesel fuel; yet, the underlying mechanism is not well understood. This study investigates the furan oligomerization mechanism and kinetics via density functional theory and microkinetic modeling. The oligomerization proceeds in the presence of water and a Brønsted acid and require… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Also, it has been reported that Brønsted acids catalyze the hydrolysis of MF to 4-oxopentanal and the subsequent trimerization of 4-oxopentanal with two MF molecules [19,20]. This suggests that Brønsted acids may not be a suitable choice for the conversion of MF.…”
Section: Introductionmentioning
confidence: 96%
“…Also, it has been reported that Brønsted acids catalyze the hydrolysis of MF to 4-oxopentanal and the subsequent trimerization of 4-oxopentanal with two MF molecules [19,20]. This suggests that Brønsted acids may not be a suitable choice for the conversion of MF.…”
Section: Introductionmentioning
confidence: 96%
“…The hydrolysis of MF into 4-oxopentanal is observed as a major side reaction. This is ascribed to the furan ring-opening of MF with water (a byproduct of the homocoupling) under acidic conditions, as previously observed by Nikbin et al Oligomerization of MF into trimers is also known to proceed in the presence of water and acid. A high TFA concentration is favorable for both selectivity and yield to DMBF (Table ). This result suggests that the acid plays an important role in the reaction mechanism (see below).…”
Section: Results and Discussionmentioning
confidence: 53%
“…In the absence of water, ␣-carbocations are at a much lower concentration than ␤-carbocations, thus tetramerization of 2-MF was preferred [18]. In the aqueous acid catalysis of 2-MF, only the ␣-carbocation is active and can undergo ring opening [19]. The presence of water may stabilize the formation of ␣-carbocations, which further reacted with water and formed a trimer via hydrolytic ring-opening.…”
Section: Trimerization Of 2-mfmentioning
confidence: 98%